Penerapan Problem Based Learning Untuk Meningkatkan Hasil Belajar Kimia Pada Materi Hidrokarbon - Herlina Herlina (PendIPA Journal of Science Education, 2020)
The aim of this study was to improve student learning outcomes on hydrocarbon material by applying the problem-based learning (PBL) method. The research method used was Classroom Action Research (CAR) which generally consists of 2 (two) cycles. This research was conducted in Class XI IPA 2 at public high school 7 Rejang Lebong with a sample of 25 students. Data collection techniques used were tests and observation sheets. From the results of research in the second cycle, an increase in activity and student learning outcomes from the first cycle was 69.47 with a percentage of 60%. In the second cycle, the average value of 78.53 students' posttest was achieved, and the percentage of completeness of student learning outcomes reached 92%, with score of students ?70. The results of student observations using the problem-based learning method have good responses from students. This proves that learning by using problem-based learning has a positive impact on students in teaching and learning.